КАРАҚАЛПАҚ ФОЛЬКЛОРЫ ТИЙКАРЫНДА КИШИ ЖАСТАҒЫ БАЛАЛАРДЫҢ ПИКИРЛЕЎИН РАЎАЖЛАНДЫРЫЎ - Абдалиева, П.И. (ILIM hám JÁMIYET, 2020)
Tne author of the studies the materials of childrens` national Karakalpak folklore and shows their role in the development of the critical thinking of school children.